Application of Virtual Reality, Artificial Intelligence, and Other Innovative Technologies in Healthcare Education (Nursing and Midwifery Specialties): Challenges and Strategies - Galya Georgieva-Tsaneva; Ivanichka Serbezova; Silvia Beloeva (Education Sciences)
This article focuses on enhancing the quality of training in nursing and midwifery specialties through the application of innovative technologies in education. The widespread integration of innovations into the education process creates expanding opportunities for the implementation of modern, sustainable, and technology-supported training methods. An innovative training system for nurses and midwives was developed and implemented over one academic year. The system incorporated educational video materials, serious games, problem-solving activities, and more. Additionally, the study explored the potential of leveraging artificial intelligence and virtual reality to enhance training effectiveness. Participants in the educational experiment were divided into an experimental group (who received additional training through innovative methods) and a control group (who underwent traditional training). Both groups underwent pre-tests and post-tests to evaluate their practical skills in injection techniques. The results demonstrated a significant improvement in the acquisition of patient care skills when modern interactive technologies were integrated into the training process. Statistical analysis confirmed the significance of the obtained results. This research provides foundational methodological guidelines for researchers, educators, and curriculum developers interested in incorporating innovative interactive technologies into healthcare education.